Death, Personhood, and the Hope of Resurrection: A Christian Philosophical Inquiry - WELIKINSI; SUPARTA, I Ketut Gede (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
This paper explores the Christian philosophical understanding of death and personhood, arguing that the doctrine of bodily resurrection provides a coherent metaphysical and existential framework distinct from secular thanatology. Whereas modern philosophical approaches often reduce death to a biological endpoint or conceptualize immortality through materialist means (e.g., transhumanism), Christianity affirms that human persons—as bearers of the imago Dei—are destined for eschatological renewal. Drawing from Scripture, classical theology (Augustine, Aquinas), and contemporary analytic philosophy (N.T. Wright, Richard Swinburne), this study examines three core themes: (1) the ontological grounding of personhood in divine creation and redemption, (2) the paradox of death as both a consequence of sin and a conquered enemy through Christ’s resurrection, and (3) the logical and metaphysical coherence of bodily resurrection against objections from materialism and dualism. The paper engages with key philosophical challenges, including the “intermediate state” (the condition of the soul between death and resurrection) and the problem of personal identity across temporal discontinuity. It contrasts Christian hope with secular immortality projects, demonstrating how resurrection avoids the pitfalls of disembodied spiritualism and biological reductionism. Finally, the study highlights the pastoral and ethical implications of resurrection belief, showing how it transforms grief, moral agency, and the pursuit of justice. By synthesizing theology and philosophy, this paper offers a robust Christian alternative to contemporary discourses on death, asserting that personhood, even in mortality, is eternally significant.